A review of advertisements for part-time library positions in Pennsylvania and New Jersey. Issue 1 (11th January 2016) - Wilkinson, Zara
Abstract : Purpose: – The purpose of this paper is to examine advertisements for part-time professional library jobs in Pennsylvania and New Jersey. The goal is to gain a better understanding of what skills and experience levels are being required of part-time librarians, as well as what their expected salary and hours might be. Design/methodology/approach: – Advertisements for part-time professional library positions were collected from online sources over the course of one year. Findings: – Part-time librarian positions tend to be public services positions in either public or academic libraries. Advertisements for these position indicate a need for flexibility and often do not contain information about salary or hours. Many are suitable for entry-level librarians with no experience. Research limitations/implications: – Job advertisement studies are limited in that they can only examine the information contained in the advertisements themselves and therefore may not reflect the actual person hired. Practical implications: – This paper will provide useful information for librarians seeking part-time positions, as well as for library and information science educators and library managers who wish to mentor or hire new librarians. Originality/value: – This paper corrects an identified lack of research into part-time library employment.